Neutron capture cross section measurements of 232Th in the 30-600 keV energy range - Karamanis, D.; Petit, M.; Andriamonje, S.; Barreau, G.; Bercion, M.; Blank, Β.; Czajkowski, S.; Del Moral, R.; Giovinazzo, G.; Lacoste, V.; Marchand, C.; Pravikoff, M.; et al. (HNPS Advances in Nuclear Physics, 2019)
Neutron capture cross sections of 232T/i have been measured relative to 197Au in the energy region from 30 keV to 600 keV. The neutron source was the reaction 7Li(p, n) produced on the 4 MV Van de Graaff Accelerator of the Centre d' Etudes Nucléaires de Bordeaux (CENBG). Preliminary analysis of the measurements indicates that the cross sections are closer to the JENDL database values.